Ensuring monetary, human capital and natural capital returns in biomass production: Lessons from the Mentawai biomass gasification power plant project - Wahono, J.; Brady, M.A.; Baral, H. (Center for International Forestry Research, 2022)
Primary energy demand in Indonesia is growing rapidly due to urbanization, economic development and population growth. The Government of Indonesia has mandated that new and renewable energy should contribute 23% of the national energy mix by 2025. Indonesia’s updated Nationally Determined Contribution (NDC) stresses five sectors in which greenhouse gas (GHG) emissions are to be reduced, with land use, land use change and forestry (LULUCF) and energy being the highest priorities. While Indonesia is committed to addressing climate change through the LULUCF sector, there are clear contextual challenges that must be confronted to create the enabling conditions for REDD+, the main mechanism for carbon revenues, to contribute to landscape restoration in Indonesia. This chapter argues that biomass production for power plants in remote and isolated areas could become an additional agent of change in tackling this difficult problem. Using a case study from the Mentawai islands in Indonesia, we describe a methodology for rural electrification using a community- and biomass-based power generation system. The Mentawai model not only shows that biomass power plants can be used as the backbone for electricity generation in remote and isolated settings, but it can also be valuable tools to help alleviate poverty in underdeveloped regions in Indonesia as well as help finance the restoration of degraded and marginal lands. Replicating this system—one which results in biomass production, land restoration, affordable electricity and local economic growth—could improve the contribution of renewable energy to the energy mix and to the overall prosperity of Indonesians in rural and remote areas.